ANESTHESIA DURING SURGICAL CORRECTION OF HYPOSPADIAS IN CHILDREN: EVALUATION OF THE EFFECTIVENESS OF COMBINED ANESTHESIA (Herald of the National Children's Medical Center, 2025)
Surgical correction of hypospadias in children is accompanied by significant pain, which requires reliable analgesia. Combined anesthesia — a combination of general and regional anesthesia — helps to reduce pain, reduce the use of narcotic analgesics and minimize side effects.
Keywords: hypospadias; combined anesthesia; bupivacaine; pain relief; children